Implementasi Lean Manufacturing untuk Mengurangi Waste pada Produksi Pivot Piece (Studi Kasus PT. Tri Jaya Teknik Karawang) - Muthia Elsa Farida; Fahriza Nurul Azizah; Hamdani Hamdani (Universitas Indraprasta PGRI Jakarta, 2022)
PT Tri Jaya Teknik Karawang is one of the manufacturing companies engaged in the production of vehicle parts, because its main product is pivot piece. As for other forms of products produced by this company, such as Gongsol and Fuji Seat. This product research at PT Tri Jaya Teknik Karawang will be carried out on one type of Piece Pivot product, because this product is the company's main product, whose regular demand every month is always there and the amount is uncertain. This company has waste in the production line, namely the existence of product defects and lead times. This study aims to determine the types of waste and what factors occur in the production of pivot pieces at PT. Tri Jaya Engineering Karawang. By using the Lean Manufacturing method which begins with creating a Value Stream Mapping (VSM) then performs an analysis using the Failure Mode and Effects Analysis (FMEA) method. It is known that in the production of pivot pieces there are 3 types of waste identified, namely waiting time, unnecessary waste of inventory, and product defects. Proposed improvements to minimize waste in the production of pivot pieces are to carry out regular machine maintenance, create a production flow and provide warnings and evaluations of the performance of production operators.